The Influence of the Jigsaw Type Cooperative Learning Model on the Mathematics Learning Outcomes of Class VIII Students at SMP Negeri 1 Jorlang Hataran - Sitorus, Marulitua Gregorius; Sidabutar, Ropinus; Sihombing, Belasar (EduMatika: Jurnal MIPA, 2023)
The aim of this research is to find out how the jigsaw type cooperative learning model influences the mathematics learning outcomes of class VIII students at SMP Negeri 1 Jorlang Hataran. The type of research used is Pre-Experimental Design research. Research subjects in class VIII-3 with a total of 30 students. In this research the author used a quantitative approach. The design used in this research is One-shot case study. Based on the results of data analysis and discussion, it can be concluded that there is a significant influence of the use of the jigsaw type cooperative learning model on the learning outcomes of class VIII students at SMP Negeri 1 Jorlang Hataran for the 2023/2024 academic year. This positive influence is shown through the regression equation Y= 16.816 + 0.089X where the b value is 0.089. This influence is through the t-test, namely tcount > ttable (3.608 > 2.048) or (sig.) < 0.05 (0.000 < 0.05), then H0 is rejected and H1 is accepted, which means there is a positive and significant influence from the cooperative learning model. jigsaw type on student learning outcomes in relation and function material. The contribution of variance of variable X (jigsaw type cooperative learning model) to variable Y (student learning outcomes) is 32%.